PENGARUH OLAHRAGA INTENSITAS SEDANG TERHADAP PERUBAHAN KUALITAS HIDUP PADA LANSIA DI PIMPINAN RANTING AISYIYAH CABANG MELATI PADA TAHUN 2018 - FAWWAZ NAUFAL RACHMADI; GUSBAKTI RUSIP (JURNAL ILMIAH SIMANTEK, 2020)
Based on the population projection data, in 2017 there are 23,66 millions elderly Indonesia. Aging proccess is a conditionwhere the ability to maintain normal and structural function is decrease. Elderly will experience regression doing their dailyactivities. And will give impact to the independence’s of elderly. The benefits of exercise in elderly are increasing lifeexpentancy, cardiovascular system, bone and muscle so the elderly will be more indepedent. Based on the explanationabove, the researcher interest to know the Effect of Moderate Intensity Training Toward the changes in Quality of Life inElderly on Pimpinan Ranting Aisyiyah Cabang Melati, Medan 2018. This study aims to know the Effect of Moderate IntensityTraining Toward the changes in Quality of Life in Elderly on Pimpinan Ranting Aisyiyah Cabang Melati, Medan 2018.This study is experimental using quasi experiment pre-test post-test control group design. Data are collected by ModifiedBarthel Index Quesionairre. The result of the study showed that there was an effect of moderate intensity exercise towardsthe changes in quality of life in elderly on Pimpinan Ranting Aisyiyah Cabang Melati, Medan. Using Wilcoxon Test obtainedthe p value = 0.000 in the group of respondents who were given the intervention. Exercise can increase quality of life inelderly.